Effects of solar eclipse on photosynthesis of Portulaca oleracea and Phyla nodiflora in coastal wild conditions - Sambandan, K; Seethala Devi, K; Santosh Kumar, S; Nancharaiah, M; Dhatchanamoorthy, N (Journal of Phytology, 2012)
The total solar eclipse provided a unique opportunity to understand the effects of solar radiation on the biosphere. The present study attempts to record meteorological parameters and to compare chlorophyll contents of Portulaca oleracea and Phyla nodiflora in coastal wild conditions during total solar eclipse on July 22, 2009. Changes in meteorological parameters such as temperature by 0.5ËšC, relative humidity by 4% and light intensity around 100 lux were set to be low during eclipse day when compared to that of corresponding week. Minor changes were also observed in the wind speed and direction during solar eclipse day. Mature leaves of Portulaca oleracea and Phyla nodiflora from coastal wild conditions were collected and analysed for total chlorophyll, chlorophyll a, chlorophyll b and carotinoid contents at various time intervals during solar eclipse day and previous days. Chlorophyll levels were decreased slightly during solar eclipse day, whereas carotinoid levels were increased marginally in both the plant species. Solar radiation and its photochemical phases during eclipse day are responsible for the observed reduction in photosynthetic rates of wild plants.